MEDB-90. Iron Imbalance Can Potentiate Cisplatin Response in Pediatric Medulloblastoma by Regulating Ferroptosis. (3rd June 2022) - Kanchan, Ranjana; Perumal, Naveenkumar; Khan, Parvez; Doss, David; Venkata, Ramakanth Chirravuri; Thapa, Ishwor; Vengoji, Raghupathy; Kaushal, Jyoti; Siddiqui, Jawed; Nasser, Mohd Wasim; Batra, Surinder; Mahapatra, Sidhartha
Abstract: Medulloblastoma (MB), the most common malignant pediatric brain tumor, is a leading cause of childhood mortality. Of the four primary subgroups, patients with group 3 tumors have the poorest prognosis. Loss of chromosome 17p is a high-risk feature associated with poor outcomes in group 3 tumors. We recently elucidated the tumor suppressive properties of a novel miR, miR-1253, on the terminal end of 17p. In further exploring its anti-neoplastic effects, we discovered that miR-1253 can disrupt iron homeostasis, causing oxidative stress and inducing lipid peroxidation. These concurrent events are capable of triggering an iron-mediated form of cell death called ferroptosis. Notably, our in silico interrogation of ferroptosis regulator genes (FRGs) in group 3 tumors revealed high expression of genes associated with iron transport and glutathione metabolism. These included mitochondrial iron transporters and GPX4, a critical regulator of ferroptosis. Restoration of miR-1253 expression in group 3 cell lines resulted in specific downregulation of ABCB7, an iron-sulfur cluster exporter, and GPX4. Consequently, cytosolic and mitochondrial labile iron pools rose, glutathione levels declined, and mitochondrial oxidative stress and lipid peroxidation were induced. These events were recapitulated by ABCB7 knockdown and potentiated cell death. Treating miR-1253-expressing cancer cells with cisplatin, a group 3 MB chemotherapeutic agent with ferroptotic properties, further elevated oxidative stress, depleted glutathione levels, and augmented lipid peroxidation, with added inhibitory effects on cell viability and colony formation. Treatment with a ferroptosis inhibitor (ferrostatin-1) lead to recovery from the cytotoxic effects of this combination therapy. Our studies highlight a novel mechanism for group 3 MB pathogenesis via ferroptosis regulation and provide a proof-of-concept for exploiting group 3 MB tumor vulnerability to iron imbalance as a novel treatment strategy.